2022
DOI: 10.3390/ijerph19148584
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Birth Defects in Offspring of Chinese Pregnant Women

Abstract: Objective: This study aimed to develop a nomogram for the risk assessment of any type of birth defect in offspring using a large birth-defect database in Northwest China. Methods: This study was based on a birth-defect survey, which included 29,204 eligible women who were pregnant between 2010 and 2013 in the Shaanxi province of Northwest China. The participants from central Shaanxi province were assigned to the training group, while the subjects from the south and north of Shaanxi province were assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…These factors might play a key role in the increased risk of having a fetus with BDs (38). It has been evident that BDs might be influenced by maternal age (34) and education level (39), illness during early pregnancy (40), and family history of the disorder (12). Maternal age should be taken into account when analyzing the potential risk factors of BDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors might play a key role in the increased risk of having a fetus with BDs (38). It has been evident that BDs might be influenced by maternal age (34) and education level (39), illness during early pregnancy (40), and family history of the disorder (12). Maternal age should be taken into account when analyzing the potential risk factors of BDs.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that fetal death is one of the adverse consequences of BDs (16). A family history of fetal birth in pregnant women is generally identified as a risk factor for BDs, which will greatly increase the probability of PIs with BDs (OR = 3.84, 95% CI: 1.64-8.96) (12,49). Especially, having three or more PIs with BDs is a stronger risk factor of a family history of BDs (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with Mekonnen et al, [27].who found that only 10 cases (7.4%) out of 160 cases reported a family history of anomalies. On the other hand, Qu et al, [28] stated that a family history of birth defects has been associated with an increased recurrence risk of congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%